(untitled) (Journal of Contemporary Issues in Accounting, 2023)
The study examined financial inclusion determinants and performance of Micro, Small and Medium Enterprises (MSMEs) in Nigeria. The aim was to ascertain the impact of Financial Inclusion (FI) determinants namely: Business Plan (BP), Marketing Strategy (MS), Accounting System (AS) and Manpower Training (MpT) being the explanatory variables on profitability proxy for performance being the dependent variable. Data for the study were obtained from responses from 187 respondents made up of owners and employees of nine (9) MSMEs in Gombe and Adamawa states. Analysis of the data was done with Ordinary Least Square (OLS) regression and Johansen system co-integration test. Findings indicated that the explanatory variables have a significant impact on MSMEs performance. The study recommended that MSMEs should have in place the critical FI determinants/requirement of fund lenders to access finance for growth, expansion and profitability of the enterprises.